1075 What do we know about imported infections in children presenting to UK emergency departments? a paediatric emergency research in the UK and Ireland network study. (17th August 2022) - Wasala, Desha; Fanshawe, Thomas; Bird, Christopher; Merrick, Vanessa; Mullen, Niall; Turner, Philip; Hayward, Gail
Abstract : Aims: The rise in human mobility - tourism, business or fleeing poverty and conflict - looks set to continue after the Covid-19 pandemic.(1) Children are more vulnerable to infection than adults but there are fewer data on imported infections in this patient group.(2) We aimed to estimate the number of tropical versus common UK infections, to map where children had travelled to and calculate geographic risk for malaria and other tropical infections as part of a PERUKI network study. Methods: Data were collected from 15 UK paediatric emergency departments (ED) as part of a retrospective, multi-centre diagnostic accuracy study, in any child <16 years presenting to ED with history of fever and travel to a malaria endemic area (http://travelhealthpro.org.uk/), between 01/01/2016 and 31/12/2017. All children in this cohort were tested for malaria and the final discharge diagnosis and respective region of travel was recorded. Geographical risk was calculated for common tropical infections. UK Health Research Authority approval: 20/HRA/1341. Results: 1, 472 children (across 15 sites) arriving from malaria endemic regions with a history of fever were screened for malaria (microscopy and RDT tests). The majority of children assessed for imported tropical infections were from South Asia (43%) followed by Sub Saharan Africa (34%) (see figure 1 ). 49% of children had common infections such as viral URTI; 23% of infections were tropical, with an overall malaria prevalence of 4.5% (64 reported cases) (see figure 2 ). There was no diagnosis for 20.9% of patients while 6.6% were coded as having fever. Of children arriving from Sub Saharan Africa, 11% (8.4-14.1%) had malaria, 0.6% (0.2-1.9%) typhoid and 10.1% (7.7-13.2%) gastroenteritis. In children arriving from South Asia, 1.4% (0.7-2.8%) had malaria, 15.6% (12.9-18.7%) typhoid, 15.6% (12.9-18.7%) gastroenteritis and 0.6% (0.2-1.7%) dengue. Conclusion: Nearly a quarter of children presenting to a UK ED with fever and a tropical travel history have a tropical infection if gastroenteritis is included. Travel patterns are linked to historical, language and travel ties (3), but given higher numbers of tropical diagnoses in adult studies (1) and lack of a diagnosis in a quarter of cases in this study, tropical infections such as Dengue are likely not being tested for and missed. References: Grobusch MP, Weld L, Goorhuis A, Hamer DH, Schunk M, Jordan S, et al. Travel-related infections presenting in Europe: A 20-year analysis of EuroTravNet surveillance data. The Lancet Regional Health - Europe. 2021 Feb;1:100001. Naudin J, Blondé R, Alberti C, Angoulvant F, de Lauzanne A, Armoogum P, et al. Aetiology and epidemiology of fever in children presenting to the emergency department of a French paediatric tertiary care centre after international travel. Archives of Disease in Childhood. 2012 Feb 11;97(2):107–11. Tatem AJ, Jia P, Ordanovich D, Falkner M, Huang Z, Howes R, et al. The geography of imported malaria to non-endemic countries: a meta-analysis of nationally reported statistics. The Lancet Infectious Diseases. 2017 Jan 1;17(1):98–107.